1995
DOI: 10.1002/anie.199518741
|View full text |Cite
|
Sign up to set email alerts
|

Platination Pathways for Reactions of Cisplatin with GG Single‐Stranded and Double‐Stranded Decanucleotides

Abstract: 1H, 15N correlated NMR spectroscopy has proven to be a suitable method to investigate the reaction of the anticancer drug cisplatin cis‐[PtCl2(NH3)2] (1) with DNA. All the intermediates in reactions of 1 with complementary model oligonucleotides can be detected with this method; one of these intermediates is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…Rate constants for each step were extracted from numerically optimised fits to these data curves and the calculated curves are also shown in Figure 2. Calculated rate constants are listed in Table along with those reported previously for reaction at the GpG site [28,29]. Rates of monofunctional adduct formation at the ApG site are broadly similar to those at the GpG site.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Rate constants for each step were extracted from numerically optimised fits to these data curves and the calculated curves are also shown in Figure 2. Calculated rate constants are listed in Table along with those reported previously for reaction at the GpG site [28,29]. Rates of monofunctional adduct formation at the ApG site are broadly similar to those at the GpG site.…”
Section: Introductionsupporting
confidence: 54%
“…They also studied the reaction of cisplatin with oligonucleotides and found a higher rate of binding to the 3' guanine of a GpG pair and faster closure to the bifunctional adduct from this base [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…They detected no aqua monoadduct and found that one chloro monoadduct ring-closed much faster than the other. 1371 The absence of accumulation of aqua monoadducts also indicates that c~~-[P~(NH,),(H,O),]~ + is not the predominant species reacting with DNA under these experimental conditions. In our opinion, it would be premature to extrapolate this result to in vivo conditions.…”
Section: Eic This Conversion Is Expressed By Equations (I)-(iii)mentioning
confidence: 93%
“…Reactions of 2 in acidic conditions are complicated by the hydrolysis of 2 to 3 (Scheme 2) and this occurs in parallel with the direct reaction of 2 with the oligonucleotide. Since 3 is considerably more reactive towards nucleobases than 2, [22,23] the commonly used approximation neglecting the reaction between 3 and the oligonucleotide [12,13,16,24] yields unprecise results. Our solution to the problem resided in separate investigations of the reaction of 3 in a series of experiments that we reported earlier [18] (indicated by bold arrows in Schemes 2 and 3) and allowed the reactions of 2 (Scheme 2) and 4 (Scheme 3) to be studied with a reduced number of variables.…”
Section: IImentioning
confidence: 99%
“…Adjustments of pH by addition of diluted HClO 4 by hand or using a pH-stat did not work satisfactorily in our hands, since even very small additions caused significant pH jumps, or the acid had to be so diluted that the volume increase perturbed the measurements. Unlike other authors, [12,13,16,24] we refrained from using phosphate or other buffers, since they contain potential ligands for platinum. [34] Specifically, the frequently used phosphate buffer has been clearly shown to perturb the kinetics of DNA platination reactions.…”
Section: 'mentioning
confidence: 99%